Pembinaan Kedisiplinan Peserta Didik di Sekolah Menengah Kejuruan Negeri 4 Pariaman - Muhammad Yadriyan; Anisah Anisah; Nelfia Adi; Hanif Al Kadri (Journal of Educational Administration and Leadership, 2021)
This study aims to obtain information disciplinary guidance students at State Vocational High School 4 Pariaman. The research question is how well the disciplinary guidance of students in terms of guidance, direction and supervision of class XI and XII students of SMK Negeri 4 Pariaman, totaling 405 people with 25% sampling of 106. The instrument used was a Likert scale model. The result is that the disciplinary guidance of students in Vocational High School 4 Pariaman has been carried out well.